2023
DOI: 10.1002/celc.202300434
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Isoxazoles and Isoxazolines via Anodic Oxidation of Oximes

Silja Hofmann,
Johannes Winter,
Tobias Prenzel
et al.

Abstract: Isoxazol(in)es are widely featured structural motifs in natural products, agrochemicals, and pharmaceuticals. The first intermolecular approach for a direct electrochemical synthesis from readily available aldoximes is reported. Isoxazoles and isoxazolines were obtained in yields up to 81 %. The synthesis is carried out in an undivided cell as the simplest electrochemical set‐up and requires only the use of electric current as traceless oxidizing agent. The application of inexpensive and widely available elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(95 reference statements)
1
1
0
Order By: Relevance
“…Finally, the conversion of a nonglyoxylate-based oxime and the reaction of 5e with phenylacetylene as dipolarophile were investigated. It was found that the herein presented method very well complements the recently described protocol as it allows easy access to isoxazolines in an in-cell process. Isoxazoline 6ai was thus obtained in an improved yield of 73% (instead of 66%, Scheme i).…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, the conversion of a nonglyoxylate-based oxime and the reaction of 5e with phenylacetylene as dipolarophile were investigated. It was found that the herein presented method very well complements the recently described protocol as it allows easy access to isoxazolines in an in-cell process. Isoxazoline 6ai was thus obtained in an improved yield of 73% (instead of 66%, Scheme i).…”
Section: Results and Discussionsupporting
confidence: 83%
“…The mechanism was further investigated, and the efficacy was shown on a larger scope. A mediator-free protocol was provided by Waldvogel et al in a simple galvanostatic setup by direct anodic oxidation of several aldoximes . The solvent system used in that method could be easily recycled by a simple distillation, minimizing fluorinated waste products.…”
Section: Introductionmentioning
confidence: 99%